Economic dispatch with environmental consideration using Honey Bee algorithm / Zaidi Faiq Mohd Noh - Mohd Noh, Zaidi Faiq (2015)
Nowadays, the power system operation at minimum cost is not only the most important thing in electrical power dispatch. Environmental concerns in industries shows increment in term of concerns and awareness among companies by strictest the pollutions regulation. This paper presents a Honey Bee (HB) Algorithm solution for Economic and Emission Dispatch problem in power system. The purpose of this study is to minimize the total cost of generation under different systems and operational constraints while satisfying the power demand. The proposed technique has been tested in 6 generator unit system. The results obtained were also compared with other optimization techniques.